2001
DOI: 10.1111/0272-4332.t01-1-216174
|View full text |Cite
|
Sign up to set email alerts
|

Poliovirus Surveillance by Examining Sewage Water Specimens: Studies on Detection Probability Using Simulation Models

Abstract: Efficiency of environmental surveillance of poliovirus circulation was studied using simulation models. First, three transmission models were defined for describing different scenarios of poliovirus infections in a large unstructured population. Second, environmental factors, such as the total volume of the sewage network and losses of viruses, were modeled for computing the virus output at the sewage sampling site. Third, the effect of sampling and laboratory procedures was accounted for in the probability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 18 publications
0
52
0
Order By: Relevance
“…As has been previously shown, sewage water represents a convenient material to test large populations for the presence of enteric viruses (8-10, 18, 19, 21, 22, 25, 42, 55). Modeling studies have indicated that a single poliovirus toilet "flush" could contain enough enterovirus to be detected in a city's sewage system for up to 4 days (47). Studies of untreated sewage waters collected at different times might show seasonal fluctuation and yield further insight into the epidemiology of these viruses.…”
Section: Discussionmentioning
confidence: 99%
“…As has been previously shown, sewage water represents a convenient material to test large populations for the presence of enteric viruses (8-10, 18, 19, 21, 22, 25, 42, 55). Modeling studies have indicated that a single poliovirus toilet "flush" could contain enough enterovirus to be detected in a city's sewage system for up to 4 days (47). Studies of untreated sewage waters collected at different times might show seasonal fluctuation and yield further insight into the epidemiology of these viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the virus was isolated by a trap sampling method. Theoretically, the likelihood of detecting virus excreted by a single person in a sewage system where excreta from a given person are mixed with sewage derived from half a million nonexcretors, is very small (19,32). The nonselective adsorbent immersed in the sewage is likely to be rapidly saturated with unrelated suspended materials abundant in a city's sewage.…”
Section: Discussionmentioning
confidence: 99%
“…Ranta and co-workers [11] have presented a mathematical model visualizing how different factors influence the proportion of excreted PV which can be recovered at a downstream sampling site, and thus sample sensitivity or population sensitivity, respectively, in ENV (Fig. 2).…”
Section: Modelling Of Factors Affecting Sensitivitymentioning
confidence: 99%